Volatility and the risk return relationship on the South African equity market - Mandimika, Neville (Rhodes University, Faculty of Commerce, Department of Economics, 2010)
The volatility of stock markets has important implications for investment decision making, financial stability and overall macroeconomic stability. This study examines the risk-return relationship as well as the behaviour of volatility of the South African equity markets using both aggregate, industrial level and sector level data. The study is divided into three parts. The first part investigates the behaviour of volatility in each of the industries, sectors and the benchmark series focussing on whether volatility is symmetric or asymmetric. Subsequently we investigate which, among the GARCH family of models appropriately captured the riskreturn relationship under which distributional assumption. The second part examines the riskreturn relationship on the SA stock market. The third part examines the long term trend of volatility and whether volatility significantly increases during financial crises and during major global shocks. The GARCH-M, EGARCH-M and TARCH-M models under the Gaussian, Student "“t and the GED are used. The findings this study makes are as follows: firstly, there is no clear relationship between risk and return. Secondly, volatility is asymmetrical, implying that bad news has a greater effect on volatility than good news in the South African equity market. Thirdly, the TARCH-M model under the GED was found to be the most appropriate model. Fourthly, volatility increases during financial crises and major global shocks. Overall, volatility is generally not priced on the South African equity markets. Thus, both local and international investors need to consider other factors that influence returns such as skewness. The general increase in volatility during financial crises and major global shocks poses a major concern for policy makers as this may cause financial instability. Thus policy makers need to be mindful of the behaviour of volatility in the South African equity market in response to external shocks.
Keywords: Stock exchanges; Financial risk -- South Africa; Saving and investment -- South Africa